Avaliação do “Vídeo-Polícia: Expansão”: a utilização do reconhecimento facial na segurança pública da Bahia - Santos Filho, Antonio Luis dos (2024)
Public security in Brazil consists of the measures adopted by governments to ensure the protection and safety of the population. It is known that it coexists in a scenario of inequality, gang dominance, impunity and police lethality. It materializes in the action of acting on the consequences of social problems and not on their causes. When this dynamic is understood, the core of the security field changes. Therefore, artificial intelligence and facial recognition emerge as viable alternatives to help solve these problems. Thus, with the status quo of modernization and cooperation of public security agencies, the Video Police Project: Expansion in Bahia was implemented. In view of this, the objective of the study was to evaluate the usefulness and relevance of the use of facial recognition in the Video-Police Project: Expansion implemented as a public security policy in the State of Bahia to reach fugitives and wanted persons. The work considered the different sources of information and data, primary and secondary, in addition to the perception of institutional managers, providing information to understand that, by serving the community and the common good, the use of facial recognition is an alternative to public policy. In this sense, we sought to understand the conception of the use of autonomous technology, the circumstances of the implementation of the technology in the state, as well as the repercussions, risks and measures adopted to pacify coexistence in the Rule of Law, tracing the trajectory of intelligent video surveillance. We chose to undertake a qualitative, exploratory and descriptive research, supported by the contributions of quantitative data, in an evaluative perspective applied in the in-depth evaluation, exploring the axes of content, context and trajectory analysis. As a result of the research, we can confirm the usefulness and relevance of the policy, respectively, in the proposed functionality and for being one of the pioneering states in the implementation, use and expansion of this innovation. Despite this, the research identifies several concerns, such as, for example, the lack of specific regulation, with emphasis on disrespect for privacy and data protection, which should be constantly monitored by society and internal and external control bodies. It is worth noting that considerations and recommendations were made with the aim of improving the Project. It also leaves new knowledge for the ratification or demystification of narratives about the use of the tool in Bahia.